Development of materials model based on microstructure evolution for formability analysis of low-Ni austenitic stainless steel. Issue 1 (April 2015) - Shanta, C; Harsh, N; Bhargava, M; Prita, P; Sushil, M
Abstract: Low Ni austenitic stainless steels exhibit outstanding mechanical properties due to the occurrence of two deformation mechanisms: dislocations glide (slip) and phase transformation (austenite fcc phase to strain induced a martensite (bcc)). Both mechanisms have strong dependence on strain and strain paths. The local misorientation development due to slip (grain average misorientation (GAM)) is more in biaxial strain-path (BS) followed by plane strain (PS) and uniaxial strain-path (US); whereas martensite volume fraction followed an opposite trend (US > PS > BS) as compared to GAM. In the present study a constitutive material model is developed based on phase transformation and GAM which has been implemented to describe the strain hardening behaviour of material for various strains and strain paths. Variation of normal anisotropy ( r̄ ) with stain and strain paths was also considered. Finally the constitutive model and instantaneous r̄ were incorporated in Finite Element (FE) based simulation to improve the strain path predictability for this material.